Store-and-Forward Teledermatology Wound Checks Following Mohs Surgery: A Pilot Study - Tyler Werbel; Navid Farahbakhsh; Sailesh Konda (Telemedicine Reports)
Introduction: Store-and-forward telemedicine is a form of electronic transmission in which patient images or clinical information are transmitted to clinicians for asynchronous clinical decision making. This study evaluated the use, feasibility, savings, and patient satisfaction of postoperative store-and-forward wound checks following Mohs surgery. Methods: Select patients were asked to participate in a virtual postoperative wound check after receiving Mohs surgery. Participants sent photos of their wound site and subsequently completed an anonymous survey. Results: One hundred and ten patients were enrolled, mean age 68 (range 32–87). Patients saved an average of $14.16, 78.6 miles of travel, and 90 min of travel time. Ninety-eight percent of respondents felt their quality of care in teledermatology was “about the same” to “much better” than compared with traditional in-person care. Sixty-four of the respondents (90.1%) reported they would prefer their next Mohs wound check to be conducted through teledermatology. Conclusion: Store-and-forward telemedicine in patients undergoing Mohs micrographic surgery is a safe, effective, and efficient method for postoperative wound care.